Impact of Rhizobial strains Mixture, Phosphorus and Zinc Applications in Nodulation and Yield of Bean(Phaseolus vulgaris L.) (Baghdad Science Journal, 2011)
Pot experiment was carried out at the College of Agriculture – Baghdad University during autumn season, 2007. Thirteen treatments were formulated to evaluate the effectiveness of four applications of Phosphorus (0, 60, 60×2 and 120 Kg P. h-1) and three applications of Zinc (0, 25×2 mg Zn. L-1 and 50 mg Zn. Kg soil-1) along with inoculating seeds of bean with strains mixture 889 and 1865 and non-inoculated treatment, on nodulation, yield and protein content in seeds (N%). The results showed that inoculated plants exceeded on non-inoculated one in all the studied characteristics. While, P and Zn, applications at the rate of 60×2 kg/ha and 25×2 mg/L respectively, significantly, increased, nodulation, yield, protein content in seeds of bean compared to non-inoculated treatment and Control. The highest grain yield (28.86 g/plant) were obtained with the interaction treatment (60×2 kg P /ha + 25×2 mg Zn /L) with Rhizobium inoculation. So, combined application of Rhizobium inoculant along with 60×2 kg P /ha and 25×2 mg Zn /L was considered to be the suitable combination of fertilizer for inoculated bean cultivation in silty clay loam soils.